FACILITATING THE CONSTRUCTION OF KNOWLEDGE COLLECTIVELY THROUGH DIALOGIC DISCOURSE: TEACHERS’ PERSPECTIVES AND PRACTICES IN ENGLISH LANGUAGE TEACHING - Ramasamy, Sheila Adelina; Zainal, Azlin Zaiti (TEFLIN Journal, 2023)
Dialogic discourse is said to aid the social and cognitive aspects of language learning and acquisition and students’ success in second language learning is therefore largely dependent on the interactional opportunities available. Recognising the potential impact of dialogic discourse in enhancing second language acquisition amongst Malaysian students, the Malaysian Ministry of Education (MOE) provided a large-scale training on dialogic discourse to a group of lower secondary English language teachers. This study explores the perceptions of English as a second language (ESL) teachers on the role of dialogic discourse in affording students’ opportunities for the construction of knowledge and investigates their practices in affording students with the opportunities to construct knowledge collectively through the discourse structure. To understand the role of dialogic discourse in affording students to construct knowledge collectively, five ESL teachers’ dialogic discourse strategies were examined. A qualitative approach was employed, which comprised semi-structured interviews and classroom observations for the data collection. Two of the teachers’ lessons were also examined to illustrate how dialogic discourse created opportunities for the construction of knowledge collectively which supported ESL learning through close discourse analysis of the lesson transcripts. The findings have shown that ESL teachers’ use of dialogic discourse strategies facilitates the construction of knowledge collectively among the students.This study expands our current understanding of how ESL learning occurs through classroom discourse.